Longitudinal trajectory of depression symptom severity and the influence of concussion history and physical function over a 19-year period among former National Football League (NFL) players: an NFL-LONG Study. Issue 3 (18th October 2021) - Brett, Benjamin L; Kerr, Zachary Y; Walton, Samuel R; Chandran, Avinash; Defreese, J D; Mannix, Rebekah; Echemendia, Ruben J; Meehan, William P; Guskiewicz, Kevin M; McCrea, Michael
Abstract : Objective: This study investigated the longitudinal course of depressive symptom severity over 19 years in former American football players and the influence of concussion history, contact sport participation and physical function on observed trajectories. Methods: Former American football players completed a general health questionnaire involving demographic information, medical/psychiatric history, concussion/football history and validated measures of depression and physical function at three time points (2001, 2010 and 2019). Parallel process latent growth curve modelling tested associations between concussion history, years of football participation, and overall and change in physical function on the overall level and trajectory of depressive symptoms. Results: Among the 333 participants (mean(SD) age, 48.95 (9.37) at enrolment), there was a statistically significant, but small increase in depressive symptom severity from 2001 (48.34 (7.75)) to 2019 (49.77 (9.52)), slope=0.079 (SE=0.11), p=0.007. Those with greater concussion history endorsed greater overall depressive symptom severity, B=1.38 (SE=0.33), p<0.001. Concussion history, B<0.001 (SE=0.02), p=0.997 and years of participation, B<0.001 (SE=0.01), p=0.980, were not associated with rate of change (slope factor) over 19 years. Greater decline in physical function, B=−0.71 (SE=0.16), p<0.001, was predictive of a faster growth rate (ie, steeper increase) of depression symptom endorsement over time. Conclusions: Concussion history, not years of participation, was associated with greater depressive symptom severity. Neither factor was predictive of changes over a 19-year period. Decline in physical function was a significant predictor of a steeper trajectory of increased depressive symptoms, independent of concussion effects. This represents one viable target for preventative intervention to mitigate long-term neuropsychiatric difficulties associated with concussion across subsequent decades of life.